2021
DOI: 10.2174/1567202617666201214111244
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Total Homocysteine Predicts In-Hospital Pneumonia and Poor Functional Outcomes in Acute Ischemic Stroke

Abstract: Background : We investigated the association between elevated total homocysteine (tHcy) levels upon hospital admission and short-term in-hospital outcomes including pneumonia in acute ischemic stroke (AIS) patients. Methods: A total of 2,084 AIS patients enrolled from December 2013 to May 2014 across 22 hospitals in Suzhou city were included in the present study. We divided patients into four groups according to their level of admission tHcy: quartile (Q1) (<9.70 umol/L), Q2 (9.70-12.3 umol/L), Q3 (12.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Our results overturn the contention of some previous researchers: Elevated homocysteine concentrations were found to be an independent prognostic marker of short-term mortality in patients with IS. 23,24 The results support the findings of Forti et al 25 and Wang et al, 26 which showed that high admission plasma tHcy was unrelated to in-hospital mortality. Such controversies were thought to be related to the lack of adjustment for the eGFR and the small sample size.…”
Section: Discussionsupporting
confidence: 86%
“…Our results overturn the contention of some previous researchers: Elevated homocysteine concentrations were found to be an independent prognostic marker of short-term mortality in patients with IS. 23,24 The results support the findings of Forti et al 25 and Wang et al, 26 which showed that high admission plasma tHcy was unrelated to in-hospital mortality. Such controversies were thought to be related to the lack of adjustment for the eGFR and the small sample size.…”
Section: Discussionsupporting
confidence: 86%
“…However, one study indicated that acute ischemic stroke patients with elevated total Hcy levels had a 1.55-fold increased risk of in-hospital pneumonia. 26 Hcy is currently considered to be a useful marker for inflammation. Considering the inflammation and oxidative stress theory of atherosclerosis, HHcy might accelerate the generation of high-sensitivity C-reactive protein, interleukin-8, caspase-9, matrix metalloproteinase, and other proteins that participate in the early-state formation of atherosclerosis 27 and the accumulation of inflammatory factors also might result in pneumonia.…”
Section: Discussionmentioning
confidence: 99%